A national initiative to advance school mental health performance measurement in the US. Issue 1 (2nd January 2016) - Connors, Elizabeth Halsted; Stephan, Sharon Hoover; Lever, Nancy; Ereshefsky, Sabrina; Mosby, Amanda; Bohnenkamp, Jill
Abstract: Standardized health performance measurement has increasingly become an imperative for assuring quality standards in national health care systems. As compared to somatic health performance measures, behavioral health performance measures are less developed. There currently is no national standardized performance measurement system for monitoring comprehensive school mental health in the USA. Drawing upon related initiatives in the school mental health field and national performance standards for behavioral health care in non-school settings, the current study describes the identification, development, and refinement of quality and sustainability performance measures for comprehensive school mental health. A three-phase method involving literature review and expert consensus, nominal group decision-making, and a modified Delphi process resulted in the development of two performance assessments, which include 12 domains and 67 indicators. Future directions for national performance measurement among school mental health systems to drive improvement in quality and sustainability are considered.